Comparative Study on Biodiesel-Methanol-Diesel Low Proportion Blends Operating with a Diesel Engine - Mohd Hafizil, Mat Yasin; R., Mamat; Ahmad Fitri, Yusop; Amir, Aziz; G., Najafi (Elsevier Ltd, 2015)
In this study, biodiesel (20%)-methanol (5%)-diesel (75%), biodiesel (20%)-methanol (10%)-diesel (70%), biodiesel (20%)- diesel (80%), and standard mineral diesel as a baseline fuel are tested in a multi-cylinder diesel engine. Those biodiesel-alcohol low proportion blends are investigated under the same operating conditions at 20%, 40% and 60% of engine loads to determine the engine performance and emission of the diesel engine. Overall, biodiesel-methanol-diesel blends show higher brake specific fuel consumption than mineral diesel. As methanol proportions in blends increase, NO emissions increase, while CO emissions are reduced. Also, biodiesel-diesel blend with 5% of methanol is more effective than biodiesel blend with 20% for reducing CO emissions.